RESOLUSI KONFLIK STRUKTURAL DAN KULTURAL: STUDI KASUS PERUSAKAN RUMAH IBADAH AHMADIYAH DI SINTANG KALBAR - Abdul Jamil Wahab (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2021)
Hundreds of people acting in the name of the Islamic Ummah Alliance raided the settlement of the Ahmadiyah congregation in Balai Harapan Village, Temunak District, Sintang Regency, West Kalimantan and damaged a house of worship belonging to the Ahmadiyah congregation and burned a nearby building on Friday, September 3, 2021. To prevent the conflict from spreading and it can be done immediately, it is necessary to conduct a study of the incident and then formulate a pattern of conflict resolution that needs to be carried out. Through a qualitative approach, by interviewing a number of key informants at the scene, this study succeeded in identifying several factors that influenced the conflict, namely: the construction of the Ahmadiyah mosque as a triggering factor, considering the Ahmadiyah community as a heretical group and should not exist in the Sintang area as the main factor, and elements of the Islamic Ummah Alliance and the Sintang Regional Government as a catalyst for the conflict in the incident. Both have a big role in reducing and increasing the escalation of conflict. The settlement of this case can be carried out by the Islamic Ummah Alliance and the District Government. Sintang, so both of them need to make efforts to reduce tensions after the incident of the destruction of houses of worship, as well as to build communication between the disputing parties. This study recommends that the SintangRegional Government carry out conflict resolution structurally and culturally. Meanwhile, the Ahmadiyah need to do acculturation with the culture of the community in Bina Harapan Village, so that acculturation occurs and there is no cultural gap.